(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
The susceptible nature of information against forthcoming threats has become a ponderous affair for the professionals of this field. It is a result of the rational and steady struggle by the carrying people that has produced multiple approaches which shields vital information from speculated security attacks. For the everyday users who are unfamiliar of these potential incursion(s) to their intimate information, feel helpless when they encounter persecutor(s) who wish to exploit the confidentiality of this elemental information. Here we have discussed about a distinctive approach which deal with these upcoming attacks. We have tried to produce an algorithm which will safeguard users against objectionable invasion of reserved information. We have incorporated a set of diverse techniques to produce an algorithm which is immune to these incursions. These methods interpolate perceptions like Hybrid cryptography [3], R.S.A. algorithm [1], Key management, Hash functions or Encrypted key exchange.